Improving the Cd2+ detection capability of a new anionic rare earth metal–organic framework based on a [RE6(μ3-OH)8]10+ secondary building unit: an ion-exchange approach towards more efficient sensors. Issue 6 (20th May 2020) - Panagiotou, Nikos; Evangelou, Kasiani; Psalti, Athanasia; Varnava, Nektaria; Angeli, Giasemi K.; Trikalitis, Pantelis N.; Plakatouras, John C.; Lazarides, Theodore; Tasiopoulos, Anastasios J.
Abstract : A new family of microporous anionic rare earth (RE) MOFs based on a hexanuclear (RE)6 secondary building unit along with a post-synthetic ion-exchange method to enhance the metal ion sensing capability of anionic MOFs are reported. Abstract : The synthesis and characterization of a new family of rare earth (RE) MOFs based on a hexanuclear (RE 3+ )6 secondary building unit (SBU) and the angular dicarboxylic ligand 4, 4′-oxybisbenzoic acid (H2 OBA) with the formula {((CH3 )2 NH2 )2 [RE6 (μ3 -OH)8 (OBA)6 ]}∞ (((CH3 )2 NH2 )2 (1 )(RE); RE: Y, Tb, Dy, Ho) is reported. Gas sorption studies indicated a moderate Langmuir area of 377 m 2 g −1 . Photoluminescence studies in the visible region of the ((CH3 )2 NH2 )2 (1 )(Y) doped with 5% Eu 3+ or 5% Tb 3+ revealed the presence of the characteristic emission bands for these RE 3+ ions. Cd 2+ sensing studies of ((CH3 )2 NH2 )2 (1 )(Y) doped with Eu 3+ however, indicated slow exchange kinetics prohibiting the use of this material for sensing applications. Successful counter ion exchange of the as synthesized compound with Na + and Mg 2+ led to the isolation of Na2 (1 )(Y) and Mg(1 )(Y). Interestingly, the exchanged analogue Na2 (1 )(Y) doped with 5% Eu 3+ exhibited fast Cd 2+ sorption kinetics and was proven to be a greatly improved sensor for this metal ion both in terms of kinetics and sensitivity. Batch Cd 2+ sorption experiments at room temperature of Na2 (1 )(Y) revealed a maximum sorption capacity of 63 ± 2 mg g −1 corresponding to the insertion of ∼1.25 equivalents Cd 2+ per (Y 3+ )6 SBU. Overall this work demonstrates the post-synthetic ion exchange of the bulky ((CH3 )2 NH2 ) + counter-ions by inorganic cations as an excellent method for the improvement of the sensing capability of RE-based anionic MOFs.